Seed Longevity of Tagasaste (Chamaecytisus palmensis) after Seed Treatment Using Boiling Water as Affected by Storage Durations - Mulisa Faji; Gezahagn Kebede; Fekede Feyissa; Kedir Mohammed; Gezahagn Mengistu (International Journal of Agronomy)
Storage duration and seed treatments before storage are important factors responsible for retaining seed longevity. Hence, germination of tagasaste seed in the laboratory or nursery has been difficult and problematic without seed treatment, and yet, there is no information about the tagasaste seed longevity after treatment. Thus, this research was carried out to investigate the longevity of tagasaste seed after seed treatment for optimum germination percentage. The tagasaste seed was collected from the field of Holetta Agricultural Research Centre and treated monthly from March 2016 through February 2017. The germination test for the treated seed was done in the month of March for three consecutive years (2017, 2018, and 2019). The experiment was conducted in a randomized complete block design with three replications. The data were analyzed using the SAS software, and the least significant difference was employed for mean separation. The germination percentage was not significantly P>0.05 different within the months of the first, second, and third years of storage durations. While, the germination percentage of the seed stored after treatment for one, two, and three years was nonsignificant P>0.05. Therefore, the treated seed of tagasaste can be stored under the ambient conditions of a tropical highland environment for about three years without significant loss in germination percentage. However, the study should be conducted for more years to know the effect of storage duration on seed viability of tagasaste after seed treatment.